2006
DOI: 10.1101/gr.5322306
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of cyanobacterial genomes: Quantification of horizontal gene transfer events

Abstract: Using 1128 protein-coding gene families from 11 completely sequenced cyanobacterial genomes, we attempt to quantify horizontal gene transfer events within cyanobacteria, as well as between cyanobacteria and other phyla. A novel method of detecting and enumerating potential horizontal gene transfer events within a group of organisms based on analyses of “embedded quartets” allows us to identify phylogenetic signal consistent with a plurality of gene families, as well as to delineate cases of conflict to the plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
261
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(279 citation statements)
references
References 73 publications
(89 reference statements)
15
261
0
3
Order By: Relevance
“…6,9,11,12 . Such patterns are probably a consequence of existing barriers to HGT, which have been reviewed in detail elsewhere 13,14 .…”
Section: Competing Interests Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…6,9,11,12 . Such patterns are probably a consequence of existing barriers to HGT, which have been reviewed in detail elsewhere 13,14 .…”
Section: Competing Interests Statementmentioning
confidence: 99%
“…For illegitimate recombination, in which the incoming DNA is not homologous to the recipient DNA, the frequency is expected to be orders of magnitude lower than the frequency for homologous sequences, especially for linear fragments as opposed to circular molecules, as reviewed elsewhere 14 . In silico analyses of gene transfer patterns indicate that HGT is much more frequent between closely related organisms than between distantly related ones 9,11,71 . This is consistent with the idea that GTAs have played an important part in creating such HGT patterns, as GTA-mediated HGT requires specific interactions between the host and the GTA particle for successful attachment and injection of the DNA 72 , as well as DNA sequence similarity to facilitate incorporation of a transferred allele by homologous recombination 14 .…”
Section: Transfer Of Packaged Dna Into Recipient Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…strain-A or B 0 ). Comparative genomic studies have shown that, although gene transfer among cyanobacteria is evident (Zhaxybayeva et al, 2006), these events have been infrequent to the degree that they do not obscure inferences about the phylogenetic relationships in this kingdom (Kettler et al, 2007;Swingley et al, 2008;Zhaxybayeva et al, 2009;Melendrez et al, 2011;Popa et al, 2011).…”
Section: Insights Into Genome Evolutionmentioning
confidence: 99%
“…This gene diversity and genome fluidity frequently underlies the emergence of new pathogens and the natural attenuation of important environmental pollutants, and hence, has important health and economical consequences (Handelsman et al, 2007). Horizontal gene transfer (HGT) accounts for a substantial fraction, if not the majority, of the bacterial genomic fluidity and diversity (Beiko et al, 2005;Zhaxybayeva et al, 2006;Lang and Beatty, 2007). However, a robust understanding of the rates of genetic exchange for most bacterial species under natural conditions and the influence of the ecological settings on the rates remain elusive (Gevers et al, 2005;Konstantinidis et al, 2006a;Handelsman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%